2014
DOI: 10.3390/toxins6061837
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of Lycopersicon Esculentum to Microcystin-LR: Effects in the Leaf Proteome and Toxin Translocation from Water to Leaves and Fruits

Abstract: Natural toxins such as those produced by freshwater cyanobacteria have been regarded as an emergent environmental threat. However, the impact of these water contaminants in agriculture is not yet fully understood. The aim of this work was to investigate microcystin-LR (MC-LR) toxicity in Lycopersicon esculentum and the toxin accumulation in this horticultural crop. Adult plants (2 month-old) grown in a greenhouse environment were exposed for 2 weeks to either pure MC-LR (100 μg/L) or Microcystis aeruginosa cru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 55 publications
1
32
0
Order By: Relevance
“…Regarding to MC‐LR, there are several studies in the scientific literature in HepG2 cells but most of them used lower concentrations than in the present work as they were focused on the study of toxicity mechanisms and not in deriving EC 50 values (ie, Refs. ). Chong et al concluded that MC‐LR did not cause cytotoxic effects in HepG2 cells and other hepatic cell line in 48–96 h of exposure to concentrations up to 100 μg/mL.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Regarding to MC‐LR, there are several studies in the scientific literature in HepG2 cells but most of them used lower concentrations than in the present work as they were focused on the study of toxicity mechanisms and not in deriving EC 50 values (ie, Refs. ). Chong et al concluded that MC‐LR did not cause cytotoxic effects in HepG2 cells and other hepatic cell line in 48–96 h of exposure to concentrations up to 100 μg/mL.…”
Section: Discussionmentioning
confidence: 97%
“…The presence of two or more cyanobacterial species in water reservoirs is a common finding around the world . Among these cyanobacteria, many are capable to produce cyanotoxins, such as MC‐LR and CYN, which can cause harmful effects in animals, plants, and humans . However, the potential interaction between MC‐LR and CYN has not been deeply explored in vitro, although it is of interest due to their co‐occurrence …”
Section: Discussionmentioning
confidence: 99%
“…Cyanobacteria, specifically MC-LR, can bioaccumulate in various food crops irrigated with cyanobacteria-contaminated water (Codd et al, 1999;Chen et al, 2004;Järvenpää et al, 2007;Crush et al, 2008;Mohamed and Al Shehri, 2009;Hereman and BittencourtOliveira, 2012;Gutierrez-Praena et al, 2014;Bittencourt-Oliveira et al, 2016;Cordeiro-Araújo et al, 2016;Machado et al, 2017a). Concentrations measured in plants are dependent on the concentrations in the water used for irrigation (Hereman and BittencourtOliveira, 2012).…”
Section: Cyanotoxins Can Bioaccumulate In Food Cropsmentioning
confidence: 99%
“…One germination experiment irrigated seedlings with MC-LR concentrations that do not reflect ecologically relevant concentrations, i.e., the highest dose used was 3000 µg/L (Chen et al, 2004). Some studies were conducted under hydroponic conditions (Gutierrez-Praena et al, 2014), whereas others used potted soil or sand (Järvenpää et al, 2007;Crush et al, 2008;Hereman and Bittencourt-Oliveira, 2012;Bittencourt-Oliveira et al, 2016;Cordeiro-Araújo et al, 2016;Machado et al, 2017a). Soil can retain up to 57% of the toxin bioavailable to the plant (Machado et al, 2017b); however, there is a lack of controlled studies conducted under field conditions using ecologically relevant concentrations.…”
Section: Cyanotoxins Can Bioaccumulate In Food Cropsmentioning
confidence: 99%
“…A recent study established the transfer of MC-LR from agricultural soil contaminated with radiolabeled MC-LR (18 mg 14 C-MC-LR kg −1 ) to tomato seedling, with a final concentration of 6 µg MC-LR g −1 FW [93]. Several other studies reported an uptake of microcystins by plant roots and a presence of these toxins in shoots and leaves after culture on sand or agricultural soils [61,65,92,[99][100][101][102]. Concerning the other cyanotoxins, less detected in the surface waters, the soil-plant transfer data are scarce.…”
Section: Transport and Uptake Into Biota And Infiltration In Groundwatermentioning
confidence: 99%